Abrasion arthroplasty promotes improvement of degenerated femoral trochlear cartilage after medial open wedge high tibial osteotomy. Issue 3 (10th February 2021) - Yamada, Yuzo; Nakamura, Norimasa; Hiramatsu, Kunihiko; Mitsuoka, Tomoki
Abstract : Objectives: Several studies have reported negative effects of open wedge high tibial osteotomy (OWHTO) on patellofemoral joints with cartilage degeneration and recommended performing other procedures. However, if chondral resurfacing surgery could promote improvement of cartilage degeneration in the patellofemoral joint, OWHTO would be an acceptable option. The purposes of this study were to arthroscopically evaluate the femoral trochlear articular cartilage after abrasion arthroplasty combined with OWHTO and to investigate the factors promoting improvement of that cartilage. Methods: The present study cohort comprised 18 knees of 18 patients with varus osteoarthritis of the knee who had (1) International Cartilage Repair Society (ICRS) grade 4 femoral trochlear chondral lesions at the time of OWHTO; (2) undergone abrasion arthroplasty of the femoral trochlear cartilage in combination with OWHTO; (3) undergone second-look arthroscopy; and (4) been followed up for more than 2 years. Cartilage status was arthroscopically graded at the time of OWHTO and second-look arthroscopy. Patients were allocated to two groups according to the status of the femoral trochlear cartilage at the time of second-look arthroscopy: the improved group comprised patients with an ICRS grade of less than 3, and the not improved group comprised those with an ICRS grade of 4. Clinical outcomes, expressed as Knee Injury and Osteoarthritis Outcome Score (symptoms, pain, activities of daily living, function in sports/recreation and quality of life) and selected radiographic variables were compared between the two groups. Results: There were 11 (61%) knees in the improved group and 7 (39%) in the not improved group. A comparison of radiographic variables between the two groups revealed that neither limb alignment nor patellar height affected cartilage changes. The two groups had similar results on the symptoms, pain, sports/recreation and activities of daily living subscales of the Knee Injury and Osteoarthritis Outcome Score. However, the quality of life subscale significantly differed between the two groups (p=0.025). Conclusion: Degenerated femoral trochlear cartilage can improve after combined abrasion arthroplasty and OWHTO. A comparison of clinical outcomes between the improved and not improved groups revealed that neither radiographic variables nor clinical symptoms, including pain, affected cartilage changes at short-term follow-up. Level of evidence: Case series, level V.